Analysis of Service Quality and Reputation on User Satisfaction of Business Entity Certification Services at the Gamana Krida Bhakti Business Entity Certification Institute - Firman Kislew Tanjaya (Syntax Corporation Indonesia, 2024)
User satisfaction is a level of positive or evaluative feelings that arise after users compare their perceptions of an institution's product or service performance with their expectations. This study aims to analyze the effect of service quality and institutional reputation on user satisfaction at the Gamana Krida Bhakti Business Certification Institute. This research method uses quantitative analysis with multiple linear regression analysis techniques. The population in this study were all users of Business Certification Services at the Gamana Krida Bhakti (GKB) Business Certification Institute (LSBU), totaling 52,761. The determination of the number of samples used in this study was determined using the Slovin formula with an margin error of 10% so that a sample size of 100 respondents was obtained. The results of the study indicate that service quality has a positive and significant effect of 24% on user satisfaction, institutional reputation has a positive and significant effect of 21.1% on user satisfaction and service quality and institutional reputation together have a positive and significant effect of 30.8% on user satisfaction at the Gamana Krida Bhakti (GKB) Business Certification Institute (LSBU).